Deteksi Dini Kesehatan Mental Emosional Anak Usia Sekolah di Sekolah Dasar Wilayah Karang Kitri - Giyaningtyas, Ika Juita; Widiyatmini, Hari (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Mental health in school-aged children is a crucial aspect that influences their academic, social, and emotional development. Unfortunately, early detection of emotional and mental disorders in children remains limited, especially in elementary school settings. This community service program aimed to raise awareness and enhance the capacity of teachers and parents in early detection of children’s mental health issues using the Strengths and Difficulties Questionnaire (SDQ). The activity was conducted at SD Negeri Margahayu 2 in August 2024, involving 248 respondents. The results showed that 18.95% of children were in the normal category, 61.29% in the borderline category, and 19.76% in the abnormal category. These findings indicate that a majority of children are at an early stage of emotional and mental health risk and require further monitoring and intervention. Therefore, strong collaboration between schools and families is essential to create a supportive environment for children’s mental well-being and to prevent more severe issues.